Genomics as a Clinical Decision Support Tool for Identifying and Addressing Modifiable Causes of Cognitive Decline and Improving Outcomes: Proof of Concept Support for This Personalized Medicine Strategy - Hausman-Cohen, Sharon; Bilich, Carol; Kapoor, Sandeep; Maristany, Eduardo; Stefani, Anne; Wilcox, Alexandra (Frontiers in Aging Neuroscience, 2022)
The landscape of therapeutics for mild cognitive impairment and dementia is quite limited. While many single-agent trials of pharmaceuticals have been conducted, these trials have repeatedly been unable to show improvement in cognition. It is hypothesized that because Alzheimer’s, like many other chronic illnesses, is not a monogenic illness, but is instead caused by the downstream effects of an individual’s genetic variants interacting with each other, the environment, and lifestyle, that improving outcomes will require a personalized, precision medicine approach. This approach requires identifying and then addressing contributing genomic and other factors specific to each individual in a simultaneous fashion. Until recently, the utility of genomics as part of clinical decision-making for Alzheimer’s and cognitive decline has been limited by the lack of availability of a genomic tool designed specifically to evaluate factors contributing to cognitive decline and how to respond to these factors. The clinical decision support (CDS) tool used in the cases presented focuses on common variants that relate to topics including, but not limited to brain inflammation, amyloid processing, nutrient carriers, brain ischemia, oxidative stress, and detoxification pathways. Potential interventions based on the scientific literature were included in the CDS, but the final decision on what interventions to apply were chosen by each patient’s physician. Interventions included supplements with “generally regarded as safe (GRAS)” rating, along with targeted diet and lifestyle modifications. We hypothesize that a personalized genomically targeted approach can improve outcomes for individuals with mild cognitive impairment who are at high risk of Alzheimer’s. The cases presented in this report represent a subset of cases from three physicians’ offices and are meant to provide initial proof of concept data demonstrating the efficacy of this method and provide support for this hypothesis. These patients were at elevated risk for Alzheimer’s due to their apolipoprotein E ε4 status. While further prospective and controlled trials need to be done, initial case reports are encouraging and lend support to this hypothesis of the benefit of a genomically targeted personalized medicine approach to improve outcomes in individuals with cognitive decline who are at high risk for Alzheimer’s.